Fourteen-year change in activities of daily living of a quadriplegic, ventilator-managed patient injured by high cervical spinal cord injury during infancy: a case report - Yoshinori Yasuoka; Yukihide Nishimura; Tokio Kinoshita; Yumi Koike; Yasunori Umemoto; Fumihiro Tajima (BMC, 2022)
Abstract Background Rehabilitation of patients with high cervical spinal cord injury (CSCI) to improve activities of daily living (ADL) is challenging due to severe paralysis. In addition, pediatric patients with CSCI are rare, and literature describing ADL changes as the patient grows are limited. In this case report, we present the long-term change in ADL over time in a girl with severe high CSCI from an injury during infancy. Case presentation A 2 years and 6 months old girl, who was injured in a traffic accident, was diagnosed with C3 CSCI, resulting in complete quadriplegia and respiratory paralysis below C3. Thus, she was managed with a ventilator. Rehabilitation for quadriplegia, respiratory dysfunction, and autonomic neuropathy was started on the fifth day after the injury while she was in the intensive care unit. Six months after the injury, the patient was transferred to a hospital. Thereafter, she was discharged with nursing and care guidance provided to her family and environmental changes at home. Afterwards, she continued to acquire skills through writing training using a mouse stick, computer operation training, and electric wheelchair operation training, which enabled her to improve her ADL despite her severe disability. In terms of education, she was able to go through a regular elementary school, a regular junior high school, and then to a senior high school of a support school. Conclusions We believe that training that utilizes current technology and changes in the environment that are appropriate for daily life are important for improving the ADL of children with severe CSCI.